Perylene Bisimide Cyclophanes: Structure–Property Relationships upon Variation of the Cavity Size - Jessica Rühe; David Bialas; Peter Spenst; Ana-Maria Krause; Frank Würthner (Organic Materials, 2020)
Abstract Five cyclophanes composed of two perylene bisimide (PBI) dyes and various CH2–arylene–CH2 linker units were synthesized. PM6-D3H4 geometry-optimized structures and a single crystal for one of these cyclophanes reveal well-defined distances between the two coplanar PBI units in these cyclophanes, spanning the range from 5.0 to 12.5 Å. UV/vis absorption spectra reveal a redistribution of oscillator strength of the vibronic bands due to a H-type exciton coupling even for the cyclophane with the largest interchromophoric distance. A quantitative evaluation according to the Kasha–Spano theory affords exciton coupling strengths ranging from 64 cm−1 for the largest cyclophane up to 333 cm−1 for the smallest one and a surprisingly good fit to the cubic interchromophoric distance in the framework of the point-dipole approximation. Interchromophoric interaction is also noticed in fluorescence lifetimes that are significantly increased for all five cyclophanes as expected for H-coupled chromophores due to a decrease of the radiative rate. For the three largest cyclophanes with interchromophoric distances of >9 Å, fluorescence quantum yields remain high in chloroform (>88%), whilst for the smaller ones with interchromophoric distances <6 Å, additional nonradiative pathways lead to a pronounced fluorescence quenching.